2022
DOI: 10.2196/34717
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Cardiorespiratory Fitness Without Exercise Testing or Physical Activity Status in Healthy Adults: Regression Model Development and Validation

Abstract: Background Low cardiorespiratory fitness (CRF) is an independent predictor of morbidity and mortality. Most health care settings use some type of electronic health record (EHR) system. However, many EHRs do not have CRF or physical activity data collected, thereby limiting the types of investigations and analyses that can be done. Objective This study aims to develop a nonexercise equation to estimate and classify CRF (in metabolic equivalent tasks) usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Thus, for large population-based observational studies, non-exercise estimates generally appear to provide adequate reflections of CRF, although they are somewhat less powerful than directly measured CRF. Nevertheless, these and other studies applying non-exercise estimates of CRF [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]56] provide further confirmation of the power of CRF in predicting risk for adverse outcomes.…”
Section: Role Of Non-exercise Crf In Epidemiologic Studiesmentioning
confidence: 75%
“…Thus, for large population-based observational studies, non-exercise estimates generally appear to provide adequate reflections of CRF, although they are somewhat less powerful than directly measured CRF. Nevertheless, these and other studies applying non-exercise estimates of CRF [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]56] provide further confirmation of the power of CRF in predicting risk for adverse outcomes.…”
Section: Role Of Non-exercise Crf In Epidemiologic Studiesmentioning
confidence: 75%
“…A total of 17,954 participants were included in this study ( Supplement S1, Figure S1 ), identified as having measured waist girth and all the eCRF parameters (age, BMI, resting heart rate, blood pressure, smoking status) at baseline. To establish an apparently healthy cohort at baseline, we excluded participants per the American Diabetic Association guidelines with known or diagnosed (fasting) diabetes ( n = 5755), prediabetes ( n = 531), CVD ( n = 90), cancer ( n = 282), abnormal ECG ( n = 503), BMI < 18.5 ( n = 499), age <20 or >90 ( n = 428), chronotropic incompetence ( n = 1253), missing information ( n = 11) [ 12 , 20 , 21 , 22 ]. These inclusion/exclusion criteria ( Supplement S1, Figure S1 ) resulted in 8602 apparently healthy individuals (17.8% women) aged 20 to 81 years old at baseline, followed between 1979 and 2006.…”
Section: Methodsmentioning
confidence: 99%
“…Weiskopf et al state, “While the prospective collection of data is notoriously expensive and time-consuming, the use of EHRs may allow a medical institution to develop a clinical data repository containing extensive records for large numbers of patients, thereby enabling more efficient retrospective research” [ 11 ]. To overcome the PA data limitation in calculating eCRF from EHRs, Sloan et al recently developed a nuanced eCRF without using PA as an algorithm parameter [ 12 ]. The eCRF algorithm included vital signs commonly found in EHRs (e.g., resting heart rate, systolic blood pressure, diastolic blood pressure) and was compared with measured CRF in 42,676 adults (21.4% females).…”
Section: Introductionmentioning
confidence: 99%
“…Weiskopf et al state, "While the prospective collection of data is notoriously expensive and time-consuming, the use of EHRs may allow a medical institution to develop a clinical data repository containing extensive records for large numbers of patients, thereby enabling more efficient retrospective research" [9]. To overcome the PA data limitation in calculating eCRF from EHRs, Sloan et al recently developed a nuanced eCRF without using PA as an algorithm parameter [10]. The eCRF included vital signs commonly found in EHRs (e.g., resting heart rate, systolic blood pressure, diastolic blood pressure) and was compared with measured CRF in 42,676 adults (21.4% female).…”
Section: Of 10mentioning
confidence: 99%
“…17,954 participants were included in this study, identified as having measured waist girth and eCRF parameters. In line with previous ACLS studies to establish a healthy cohort at baseline, we excluded participants with diabetes (n=5,755), prediabetes (n=531), CVD (n=90), cancer (n=282), abnormal ECG (n= 503), BMI<18.5 (n=499), age <20 or >90 (n=428), chronotropic incompetence (n=1253), missing information (n=11) [10,16,17]. These criteria resulted in 8,602 healthy individuals (17.8% women) aged 20 to 81 years old at baseline from the ACLS followed between 1979 and 2006.…”
Section: Study Populationmentioning
confidence: 99%